Ferroptosis-related metabolic mechanism and nanoparticulate anticancer drug delivery systems based on ferroptosis - Danni Yan; Zhenghong Wu; Xiaole Qi (Saudi Pharmaceutical Journal)
Ferroptosis is a new type of cell death discovered in recent years that distinguishes from apoptosis and necrosis, mainly caused by the imbalance between the production and degradation of lipid reactive oxygen species in cells. Although the mechanism of ferroptosis is not yet clear, the phenomenon of ferroptosis has attracted widespread attention from researchers and has become a new hotspot in anti-tumor research. Studies have shown that ferroptosis is involved in the occurrence and development of a variety of diseases such as nervous system diseases, cardiovascular diseases and cancer. And inhibiting or inducing the occurrence of ferroptosis can effectively intervene in related diseases. At the same time, nanotechnology, by virtue of its distinct advantages, has been widely used in the development of nanodrug delivery systems. This review outlines current the advance on the intersection of ferroptosis and biomedical nanotechnology. In this review, the discovery and characteristics of ferroptosis, the mechanism of occurrence and the relationship with disease are summarized. More importantly, we summarized the strategies for inducing ferroptosis based on nanoparticulate drug delivery systems for cancer treatment.